Bibliometric Analysis of Music Concerts in Indonesia - Awaloedin, Dipa Teruna; Anggraini, Vira Dwi; Juliana, Elisha Maria; Pradini, Gagih; Agustiani, Fitri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Music concerts are one of the most exciting aspects of celebration in the world of music. It has become a prevalent form of entertainment for people, bringing pleasure and forgetting the fatigue of everyday life. Indonesian music concerts have proliferated in recent years, becoming major events in Indonesia's tourism industry and creative economy. More and more music festivals are held every year, enriching Indonesia's music culture and supporting national economic growth. Previous studies have looked at various aspects of music concerts, and this study tried to provide a new perspective by using bibliometrics to analyze 200 articles, mainly those published in 2023. The main goal is to rank the 5 best articles, present a bibliometric analysis, and provide data related to publications, document types, and source types. The results can help identify trends in music concert research and provide valuable insights. This research will discuss basic theories about music concerts, related issues, bibliometric methods, and the tools used.